Early-life human CD8 + T cells exhibit rapid, short-lived effector responses and a unique transcription factor landscape - Nina N. Brodsky; Monisha Chakder; Dinesh Babu Uthaya Kumar; Anis Barmada; Julia Wang; Weihong Gu; Oluwabunmi Olaloye; Anjali Ramaswamy; Aanchal Wats; Liza Konnikova; Carrie L. Lucas (Proceedings of the National Academy of Sciences, 2025)
Neonates and infants are distinct in their clinical and cellular responses to viral infections, with neonatal CD8 + T cells displaying innate-like characteristics and a low threshold for T cell receptor activation. However, specific molecular programs that drive these unique responses are incompletely understood, particularly in humans, and targetable pathways to modulate viral illness in this vulnerable population remain to be elucidated. Early-life immune responses may be developmentally programmed to prioritize avoidance of tissue immunopathology, especially while maternal immunoglobulin provides passive immunity. We set out to define the unique response characteristics and transcription factor landscape of neonatal human CD8 + T cells. Here, we report evidence that naïve neonatal human CD8 + T cells are poised for an accelerated effector switch, with elevations of killer cell lectin-like receptor G1 (KLRG1), killer cell lectin-like receptor B1 (KLRB1/CD161), Fc epsilon receptor I-gamma ( FCER1G ), DNAX accessory molecule-1 (DNAM1/CD226), granzymes, tumor necrosis factor alpha (TNFα), interleukin 2 (IL-2), and glycolysis compared to naïve adult CD8 + T cells. Further, rapid proliferation and cell death occur upon activation of neonatal CD8 + T cells, with cell viability largely rescued by IL-2 or IL-7. These features are coupled with a unique transcription factor landscape, including high expression of thymocyte selection associated high mobility group box (TOX) and HELIOS ( IKZF2 ), and these signatures continue in postnatal life until at least 2 mo of age. We conclude that early-life human CD8 + T cells maintain a unique transcriptional state associated with an accelerated effector switch and short-lived effector program, revealing key nodes of regulation relevant for the unique immunobiology of neonatal humans.